2023
DOI: 10.3390/su15065543
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Spatial Spillover Effect of Transportation Infrastructure on Urban Resilience in Three Major Urban Agglomerations in China

Abstract: The development of transportation infrastructure can ensure the strong recovery and reconstruction function of a city, and it is an important way to build a resilient city. Studying the impact of the transportation infrastructure level on urban resilience is related to the future development of a city. Based on panel data for China’s three major urban agglomerations from 2008 to 2019, this paper uses the spatial econometric model to explore the spatial spillover effect of transportation infrastructure on urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…It is the productive service industry most closely related to the manufacturing industry, forming linkages between the upstream and downstream of a supply chain. LMCA is of practical significance in reducing logistic costs, improving service quality, and achieving high-quality, integrated, and coordinated development of a regional economy [37,56]. This study explores the spatial correlation and spatial spillover effects of LMCA from the perspective of enhancing EcoResi and finds that the spatial heterogeneity of collaboration and the trade-off between various cooperative effects can improve EcoResi.…”
Section: Discussionmentioning
confidence: 99%
“…It is the productive service industry most closely related to the manufacturing industry, forming linkages between the upstream and downstream of a supply chain. LMCA is of practical significance in reducing logistic costs, improving service quality, and achieving high-quality, integrated, and coordinated development of a regional economy [37,56]. This study explores the spatial correlation and spatial spillover effects of LMCA from the perspective of enhancing EcoResi and finds that the spatial heterogeneity of collaboration and the trade-off between various cooperative effects can improve EcoResi.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the economy of Beijing-Tianjin-Heibei is rapid, but the synergy between railway transportation capacity and economic development is poor, and railway transportation is relatively backward. The literature [9][10][11][12][13][14] qualitatively introduces that Beijing-Tianjin-Hebei belongs to the most representative urban agglomeration and summarizes its development status. On the basis of the development of small-and medium-sized cities, it is important to use the external utility of HSR to improve the level of regional human capital and promote the high-quality development of the urban agglomeration economy.…”
Section: Research On the Current Situation Of Beijing-tianjin-hebei R...mentioning
confidence: 99%